2010
DOI: 10.3109/00365521.2010.537682
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofMTHFRgene C677T polymorphism onBcl-2gene methylation and protein expression in colorectal cancer

Abstract: Bcl-2 promoter is hypomethylated in colorectal cancer tissue, and there is a significant correlation between MTHFR 677 TT or CT/TT genotypes and CRC or Bcl-2 promoter CGI methylation/oncoprotein expression in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
1
19
0
2
Order By: Relevance
“…Except four studies (Haghighi et al, 2008;Kang et al, 2011;Sameer et al, 2011;Kim et al, 2012), distribution of genotypes in the controls of thirty studies was consistent with HardyWeinberg equilibrium. OR of fourteen studies (Matsuo et al, 2002;Kim et al, 2004;Miao et al, 2005;Wanget al, 2006;Chang et al, 2007;Cao et al, 2008;El-Awady et al, 2009;Chandy et al, 2010;Naghibalhossaini et al, 2010;Zhu et al, 2010;Prasad and Wilkhoo, 2011;Sameer et al, 2011;Zhu et al, 2011;Ozen et al, 2014) was above one and other twenty studies did not show any association between MTHFR C677T polymorphism and CRC. All these thirty four studies were performed in …”
Section: Characteristic Of Included Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Except four studies (Haghighi et al, 2008;Kang et al, 2011;Sameer et al, 2011;Kim et al, 2012), distribution of genotypes in the controls of thirty studies was consistent with HardyWeinberg equilibrium. OR of fourteen studies (Matsuo et al, 2002;Kim et al, 2004;Miao et al, 2005;Wanget al, 2006;Chang et al, 2007;Cao et al, 2008;El-Awady et al, 2009;Chandy et al, 2010;Naghibalhossaini et al, 2010;Zhu et al, 2010;Prasad and Wilkhoo, 2011;Sameer et al, 2011;Zhu et al, 2011;Ozen et al, 2014) was above one and other twenty studies did not show any association between MTHFR C677T polymorphism and CRC. All these thirty four studies were performed in …”
Section: Characteristic Of Included Studiesmentioning
confidence: 97%
“…55 articles from remaining 89 articles were again excluded because studied population was not Asian. Based on the inclusion and exclusion criteria, finally, thirty four studies met the inclusion criteria and were included in the present met-analysis (Park et al, 1999;Le Marchand et al, 2002;Matsuo et al, 2002;Huang et al, 2003;Kim et al, 2004;Yin et al, 2004;Jiang et al, 2005;Matsuo et al, 2005;Miao et al, 2005;Otani et al, 2005;Wang et al, 2006;Chang et al, 2007;Jin et al, 2007;Zeybek et al, 2007;Cao et al, 2008;Haghighi et al, 2008;Mokarram et al, 2008;Zhang et al, 2008;El-Awady et al, 2009;Chandy et al, 2010;Cui et al, 2010;Naghibalhossaini et al, 2010;Promthet et al, 2010;Yang et al, 2010;Zhu et al, 2010;Kang et al, 2011;Kim et al, 2011;Li et al, 2011;Prasad and Wilkhoo, 2011;Sameer et al, 2011;Zhu et al, 2011;Yin et al, 2011;Kim et al, 2012;Ozen et al, 2014).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…After discarding overlapping references and those which clearly did not meet the criteria, 22 studies were further assessed for eligibility (Park et al, 1999;Matsuo et al, 2002;Huang et al, 2003;Jiang et al, 2004;Kim et al, 2004;Yin et al, 2004;Jiang et al, 2005;Matsuo et al, 2005;Miao et al, 2005;Otani et al, 2005;Chang et al, 2007;Jin et al, 2007;Cao et al, 2008;Zhang et al, 2008;Cui et al, 2010;Promthet et al, 2010;Yang et al, 2010;Zhu et al, 2010;Kang et al, 2011;Kim et al, 2011;Zhu et al, 2011;Kim et al, 2012). After reviewing each original paper and extracting data, one study was excluded for overlapping data (Jiang et al, 2004).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…As T allele dose increases, this functional polymorphism causes a graded elevation in tHcy in the mild-moderate range, most pronounced in individuals with low dietary folate consumption (Frosst et al, 1995). Thus, considering the potential influence on Zhen Yang*, Xie-Fu Zhang, Hong-Xiang Liu, Yong-Shun, Hao, Chun-Lin Zhao folate metabolism, many epidemiological studies have explored the association between the MTHFR C677T polymorphism and CRC risk, but the results are conflicting (Park et al, 1999;Matsuo et al, 2002;Kim et al, 2004;Yin et al, 2004;Otani et al, 2005;Chang et al, 2007;Cao et al, 2008;Cui et al, 2010;Promthet et al, 2010;Kim et al, 2011;Zhu et al, 2011). Small genetic association studies have various designs, different methodology and insufficient power, and could inevitably increase the risk that chance could be responsible for their conclusions, while combining data from all eligible studies by meta-analysis has the advantage of reducing random error and obtaining precise estimates for some potential genetic associations .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported Bcl-2 exon 2 methylation status in cancer (41). It was reported that Bcl-2 promoter is hypermethylated in colorectal cancer tissue (42). They suggest that aberrant methylation of Bcl-2 promoter may be involved in the expression of Bcl-2.…”
Section: Hoxc6 Regulates Expression Of Bcl-2mentioning
confidence: 99%